Biochemical testing for the diagnosis of Wilson's disease: A systematic review. Issue 2 (23rd December 2021) - Salman, Hafiz Muhammad; Amin, Mahwish; Syed, Javaria; Sarfraz, Zouina; Sarfraz, Azza; Sarfraz, Muzna; Farfán Bajaña, Maria Jose; Felix, Miguel; Cherrez‐Ojeda, Ivan
Abstract: Background: Wilson's disease (WD) is a rare inherited disorder that leads to copper accumulation in the liver, brain, and other organs. WD is prevalent worldwide, with an occurrence of 1 per 30, 000 live births. Currently, there is no gold standard diagnostic test for WD. The objective of this systematic review is to determine the diagnostic accuracy for WD of three biochemical tests, namely hepatic copper, 24‐hour urinary copper, and ceruloplasmin using the Leipzig criteria. Methods: Adhering to PRISMA guidelines, databases including PubMed/MEDLINE, CINAHL Plus, Web of Science, and Cochrane were searched. Studies that comprised of confirmed or suspected WD along with normal populations were included with adult and pediatric group. The sensitivity, specificity, negative predictive value and positive predictive value were computed using RevMan 5.4. Results: Nine studies were included. The best practice evidence for 24‐hour urinary copper test ranged from a cutoff value of 0.64–1.6 μmol/24 h ( N  = 268; sensitivity = 75.6%, specificity = 98.3%). Hepatic copper test was optimally cutoff based on the ROC curve analysis at 1.2 μmol/g yielding a power of 96.4% sensitivity and 95.4% specificity ( N  = 1, 150); however, the tried and tested 4 μmol/g cutoff, with 99.4% sensitivity and 96.1% specificity, is more widely accepted. The ceruloplasmin test cutoff value was found to be ranging from 0.14 to 0.2 g/L ( N  = 4, 281; sensitivity = 77.1%–99%, specificity = 55.9%–82.8%). Conclusion: This paper provides a large‐scale analysis of current evidence pertaining to the biochemical diagnosis of WD employing the Leipzig criteria. The laboratory values are typically based on specific subgroups based on age, ethnicity, and clinical subgroups. The findings of this systematic review must be used with caution, given the over‐ or under‐estimation of the index tests. Abstract : Wilson's disease bears a burden on the adult and pediatric population worldwide, with a prevalence of 1 per 30, 000 live births. There is no gold standard test for the disease. This systematic review analyzes large‐scale data to find the best practice evidence for the diagnosis of Wilson's disease in symbiosis with the Leipzig criteria.